Quasinormal modes of asymptotically (A)dS black hole in Lovelock background. Issue 3 (14th March 2017) - Abbasvandi, N.; Soleimani, M.J.; Abdullah, W.A.T. Wan; Radiman, Shahidan
Abstract: We study the quasinormal modes of the massless scalar field in asymptotically (A)dS black holes in Lovelock spacetime by using the sixth order of the WKB approximation. We consider the effects of the second and third order of Lovelock coupling constants on quasinormal frequencies spectrum as well as cosmological constant.